2012
DOI: 10.1155/2012/579593
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam Irradiation Dose Dependently Damages theBacillusSpore Coat and Spore Membrane

Abstract: Effective control of spore-forming bacilli begs suitable physical or chemical methods. While many spore inactivation techniques have been proven effective, electron beam (EB) irradiation has been frequently chosen to eradicateBacillusspores. Despite its widespread use, there are limited data evaluating the effects of EB irradiation onBacillusspores. To study this,B. atrophaeusspores were purified, suspended in sterile, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
3
18
1
Order By: Relevance
“…Electronic beam irradiation (EBI) was shown to induce loss of viability of Bacillus spores by damaging spore coat, by altering membrane permeability or by DNA fragmentation (Fiester et al, 2012). High level energy beam such as those used in this work (2.2 MeV) is likely to trigger DSB as the most significant lesions in the spore embedded DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Electronic beam irradiation (EBI) was shown to induce loss of viability of Bacillus spores by damaging spore coat, by altering membrane permeability or by DNA fragmentation (Fiester et al, 2012). High level energy beam such as those used in this work (2.2 MeV) is likely to trigger DSB as the most significant lesions in the spore embedded DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Preservation of the cell wall integrity after eBeam irradiation has also been shown for Paracoccidioides brasiliensis [47], and membrane damage of Bacillus spp. spores was observed only at high doses of eBeam irradiation [45]. Although the evaluation of the ultrastructure in our study did not reveal changes in the cell wall indicative of perforation or destruction of the cell in any of the treatment groups, data from the fluorescence assay, coupled with the presence of more severe ultrastructural changes affecting the layered cell wall of heat-inactivated bacteria, indicate that the cell wall of heat-inactivated bacteria were more severely compromised relative to the other treatment groups.…”
Section: Discussionmentioning
confidence: 98%
“…These data verify the destruction of cells and provide clear evidence of the antibacterial activity of irradiation. A previous study suggested that e-beam irradiation increases the inactivation of bacteria through DNA fragmentation (Fiester et al 2012). To test this hypothesis, genomic DNA extracted from irradiated cells was measured to determine the effect of GI on the DNA integrity.…”
Section: Resultsmentioning
confidence: 99%